Rehabilitation Interventions for Poststroke Hand Oedema: A Systematic Review - Thuy Anh Giang; Alan Wei Guang Ong; Karthikeyan Krishnamurthy; Kenneth N.K. Fong (SAGE Publishing, 2016)
Objective/Background: To review the evidence of rehabilitation interventions for the management of poststroke hand oedema. Methods: We conducted a systematic review of research articles in electronic databases published in English between 1999 and 2015. Two investigators working independently retrieved articles from the Cochrane Central Register of Controlled Trials, SCOPUS, Taylor & Francis Online, Wiley Online Library, CINAHL, Springer (MetaPress), ScienceDirect, PubMed, SAGE Journals Online, EBSCO, and Web of Science. Only controlled trials with outcome measures and interventions for poststroke hand oedema were included. Three investigators critically appraised the selected studies using the Physiotherapy Evidence Database Scale. Results: Of the 189 articles identified, nine (5 randomized controlled trials, 3 nonrandomized controlled trials, and 1 crossover controlled trial) were selected. These studies are heterogeneous in terms of design and types of intervention for poststroke hand oedema. The interventions reducing hand oedema are Lycra pressure garments with glove splints, bilateral passive motion upper-limb exercises, laser therapy, and acupressure. However, due to these studies' short intervention periods and the fact that hand oedema is not their primary outcome measure, it is not possible to draw a firm conclusion on their clinical significance for managing poststroke hand oedema. Conclusion: Further study needs to focus solely on interventions for poststroke hand oedema and their long-term effects. No conclusion can be made on the most effective management of poststroke hand oedema until much more evidence is available.